Penggunaan Quick Response Code Indonesian Standard (QRIS) Sebagai Sistem Pembayaran Digital: Analisis Bibliometrik - Ferdy Achmad Triwahyudi; Indrawati Yuhertiana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the development of publications on the topic of using Quick Response Indonesian Standard (QRIS) as a digital payment system from 2018-2023 and find out scientific articles that have the highest number of citations on the topic of using Quick Response Indonesian Standard (QRIS) as a digital payment system. Data collection was carried out using Google Scholar with QRIS keywords and digital payment systems. With the categories used, namely article titles, abstracts, and keywords in vulnerable time 2018-2023. Search results show that there are 568 articles, but that number are documents of various forms. While the form of articles that researchers want is only in the form of journal articles, so that from a total of 568 only 261 articles are left in the form of journals. The number of such articles will be managed through VOSviewer 1.6.20 software. Of the 268 journal articles, many of them discuss the use of QRIS as a digital payment system in the MSME (Micro, Small and Medium Enterprises) sector. This is very interesting because MSMEs are a small business sector that has limited resources so they lack technological competence, but many studies have explored the use of QRIS in this sector. The use of QRIS, ease of use of QRIS, financial literacy, and the impact of using QRIS are clusters that have been of concern to previous researchers.